Instructional technology research, design and development: lessons from the field - Alias, Nor Aziah (IGI Global, 2012)
This book is about design and development in Instructional Technology Design and development research (Richey & Klein, 2007), or was formerly known as developmental research (Richey, Klein & Nelson, 2004) is an emerging form of research in the field of instructional technology. This method is also similar to designed case research (Reigeluth & Frick, 1999), design-based research (Reeves, 2006 & Herrington, et. al, 2007), formative research (Nieveen, 2009), and design research (Bannan-Ritland, 2003; Van der Akker, 2007) with differences in certain focal aspects. This book has been prepared to guide researchers who are embarking on a design and development research in instructional technology. These will also include emerging researchers and graduate students in the field of education, computer science, and information technology. It propagates design and development research (DDR) or design-based research but is not limited to specific deliberations on the methodology. It takes a more general approach to presenting design, development and other aspects of instructional technology research through various lessons learned by practitioners in the field. The book offers case-like examples which are detailed accounts of the different phases of the research (analysis, design, development, implementation/delivery and evaluation) that can be a valuable resource for research methodology instructors and students.